Clinical Image-Based Procedures. From Planning to Intervention International Workshop, CLIP 2012, Held in Conjunction with MICCAI 2012, Nice, France, October 5, 2012, Revised Selected Papers - Drechsler, Klaus; Erdt, Marius; Linguraru, Marius George; Oyarzun Laura, Cristina; Sharma, Karun; Shekhar, Raj.; Wesarg, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the International Workshop on Clinical Image-based Procedures: From Planning to Intervention, CLIP 2012, held in Nice, France, in conjunction with the 15th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2012. This successful workshop was a productive and exciting forum for the discussion and dissemination of clinically tested, state-of-the-art methods for image-based planning, monitoring and evaluation of medical procedures. The 16 papers presented in this volume were carefully reviewed and selected from 24 submissions.
Head Motion Compensation for Arterial Spin Labeling Using Optical Motion Tracking -- Intervention Planning of Hepatocellular Carcinoma Radio-Frequency Ablations -- A Flexible Surgical Tool Localization Using a 3D Ultrasound Calibration System for Fetoscopic Tracheal Occlusion (FETO) -- Analysis of Structural MRI Data for the Localisation of Focal Cortical Dysplasia in Epilepsy -- Automatic Detection and Quantification of Mitral Regurgitation on TTE with Application to Assist Mitral Clip Planning and Evaluation -- A Prospective Evaluation of Computer-Assisted Deep Brain Stimulation Trajectory Planning -- Method for 3D-2D Registration of Vascular Images: Application to 3D Contrast Agent Flow Visualization -- Towards Automatic Path Planning for Multi-Port Minimally-Traumatic Lateral Skull Base Surgery -- Automated Segmentation and Anatomical Labeling of Abdominal Arteries Based on Multi-organ Segmentation from Contrast-Enhanced CT Data -- Technical Evaluation of a Third Generation Optical Pose Tracker for Motion Analysis and Image-Guided Surgery -- Personalized Surgical Planning to Support Interventions and Training of Surgeons: Biomodels for Planning and Guiance -- Ultrasound B-Mode Segmentation for Registration with CT in Percutaneous Hepatic Interventions -- Computer-Based Quantitative Assessment of Skull Morphology for Craniosynostosis -- Intra-patient Non-rigid Registration of 3D Vascular Cerebral Images -- Comparison of Rigid Registration Methods in Four Clinical Scenarios -- Differences in Radiotherapy Delivery and Outcome Due to Contouring Variation.
Keywords: Computer science; Computer simulation; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; User Interfaces and Human Computer Interaction; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Simulation and Modeling